GelMA synthesis and sources comparison for 3D multimaterial bioprinting - Gaglio, Cesare Gabriele; Baruffaldi, Désireé; Pirri, Candido Fabrizio; Napione, Lucia; Frascella, Francesca (Frontiers in Bioengineering and Biotechnology, 2024)
Gelatin Methacryloyl (GelMA) is one of the most used biomaterials for a wide range of applications, such as drug delivery, disease modeling and tissue regeneration. GelMA is obtained from gelatin, which can be derived from different sources (e.g., bovine skin, and porcine skin), through substitution of reactive amine and hydroxyl groups with methacrylic anhydride (MAA). The degree of functionalization (DoF) can be tuned by varying the MAA amount used; thus, different protocols, with different reaction efficiency, have been developed, using various alkaline buffers (e.g., phosphate-buffered saline, DPBS, or carbonate-bicarbonate solution). Obviously, DoF modulation has an impact on the final GelMA properties, so a deep investigation on the features of the obtained hydrogel must be carried on. The purpose of this study is to investigate how different gelatin sources and synthesis methods affect GelMA properties, as literature lacks direct and systematic comparisons between these parameters, especially between synthesis methods. The final aim is to facilitate the choice of the source or synthesis method according to the needs of the desired application. Hence, chemical and physical properties of GelMA formulations were assessed, determining the DoFs, mechanical and viscoelastic properties by rheological analysis, water absorption by swelling capacity and enzymatic degradation rates. Biological tests with lung adenocarcinoma cells (A549) were performed. Moreover, since 3D bioprinting is a rapidly evolving technology thanks to the possibility of precise deposition of cell-laden biomaterials (bioinks) to mimic the 3D structures of several tissues, the potential of different GelMA formulations as bioinks have been tested with a multi-material approach, revealing its printability and versatility in various applications.